Use of 3-Dimensional Printers in Educational Settings: The Need for Awareness of the Effects of Printer Temperature and Filament Type on Contaminant Releases - Stefaniak, Aleksandr B; Bowers, Lauren N; Cottrell, Gabe; Erdem, Ergin; Knepp, Alycia K; Martin, Stephen; Pretty, Jack; Duling, Matthew G; Arnold, Elizabeth D; Wilson, Zachary; Krider, Benjamin; LeBouf, Ryan F; et al. (ACS Chemical Health & Safety., 2021)
Material extrusion-type fused filament fabrication (FFF) 3-D printing is a valuable tool for education. During FFF 3-D printing, thermal degradation of the polymer releases small particles and chemicals, many of which are hazardous to human health. In this study, particle and chemical emissions from 10 different filaments made from virgin (never printed) and recycled polymers were used to print the same object at the polymer manufacturer's recommended nozzle temperature ("normal") and at a temperature higher than recommended ("hot") to simulate the real-world scenarios of a person intentionally or unknowingly printing on a machine with a changed setting. Emissions were evaluated in a college teaching laboratory using standard sampling and analytical methods. From mobility sizer measurements, particle number-based emission rates were 81 times higher; the proportion of ultrafine particles (diameter <100 nm) were 4% higher, and median particle sizes were a factor of 2 smaller for hot-temperature prints compared with normal-temperature prints (all -values <0.05). There was no difference in emission characteristics between recycled and virgin acrylonitrile butadiene styrene and polylactic acid polymer filaments. Reducing contaminant release from FFF 3-D printers in educational settings can be achieved using the hierarchy of controls: (1) elimination/substitution (e.g., training students on principles of prevention-through-design, limiting the use of higher emitting polymer when possible); (2) engineering controls (e.g., using local exhaust ventilation to directly remove contaminants at the printer or isolating the printer from students); (3) administrative controls such as password protecting printer settings and establishing and enforcing adherence to a standard operating procedure based on a proper risk assessment for the setup and use (e.g., limiting the use of temperatures higher than those specified for the filaments used); and (4) maintenance of printers.